Organic farming production of broccoli genotypes in northern Portugal - Carvalho, M. (2022)
The BRESOV project intends to encourage sustainable agriculture preserving the biodiversity and promote the development of broccoli adapted to climate changes. Four broccoli genotypes, ‘CN-BRO-09’, ‘Heraklion’, ‘Naxos’ and ‘Rasmus’, adaptation to a Portuguese organic farming system were evaluated in an organic farm located in Braga, northern Portugal (41.32’18”N, 8.24’00”W). The soil was prepared on 16 ridges of 12 m2 each genotype and, biodegradable bioplastic was applied before planting. The seedlings were planted in the middle of April 2020 in a randomized complete blocks design with four replications. The germination rate ranged from 98.3% (‘Naxos’) to 94.3% (‘Heraklion’). The agro-morphological characterization was performed based on the UPOV Brassica oleracea L. var. italica Plenck descriptors (UPOV 2018). The qualitative characterization comprised the parameters ‘Leaf: attitude’, ‘Leaf blade: color’, ‘Leaf blade: ondulation of margin’, ‘Leaf: number of lobes’, ‘Head: color’ and ‘Head: knobbling’. The quantitative characteristics, ‘Total number of leaves’, ‘Weight of the main head’, ‘Diameter of main head’, ‘Number of secondary sprouts’ and ‘Weight of secondary sprouts’, were recorded in 40 randomized plants per genotype (10 per replicate). The data obtained allowed to consider ‘Rasmus’ as the earliest genotype, ‘Naxos’ as the latest. Relatively to the yield, ‘Rasmus’ was the most productive for marketable 1st choice heads and ‘CN-BRO-09’ the less productive. In a global evaluation, and under conditions similar to those of Braga, ‘Rasmus’ seems to be an interesting genotype for organic farming due to its earliness, high production and its capacity to develop secondary sprouts, appreciated by organic consumers.